2014
DOI: 10.1002/app.40766
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in molecularly imprinted polymers in food analysis

Abstract: Food security as a world issue has received increasing concern, and therefore, effective analytical methods and technologies have been continuously developed. However, the matrix complexity of food samples and the trace/ultratrace presence of targeted analytes require highly efficient cleanup and enrichment materials and procedures. Molecularly imprinted polymers (MIPs) with specific recognition abilities as versatile materials are being increasingly developed for diverse species in various fields, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 195 publications
(229 reference statements)
0
53
0
1
Order By: Relevance
“…A series of excellent reviews give exceptionally thorough accounts of molecular imprinting, [1][2][3]12,13,[17][18][19][20][21][22][23][24][25][26][27][28][29] and most of them have placed more emphasis on the fundamental aspects and characteristic applications of MIPs instead of the MIT technology. To the best of our knowledge, there are few review articles on novel techniques related to the preparation of MIPs.…”
Section: Introductionmentioning
confidence: 99%
“…A series of excellent reviews give exceptionally thorough accounts of molecular imprinting, [1][2][3]12,13,[17][18][19][20][21][22][23][24][25][26][27][28][29] and most of them have placed more emphasis on the fundamental aspects and characteristic applications of MIPs instead of the MIT technology. To the best of our knowledge, there are few review articles on novel techniques related to the preparation of MIPs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they have been used with success as stationary phases in chromatography [1] or electrochromatography [1], as parts of sensors [1,2] and especially as sorbents for sample preparation [1,3,4], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to improve the preparation method of high-performance quantum dot molecular imprinting fluorescence sensor and establish a new detection method [19] . MIPs and QDs technology are both polymer materials technology, which have developed over recent decades and are widely used in various fields, including the field of food safety [20] . It has been reported that the MIP-coated CdTe composites integrate the advantages of the high selectivity of the molecular imprinting and strong fluorescence property of the QDs [21] .…”
Section: Preparation Of Quantum Dots and Fluorescent Molecularly Imprmentioning
confidence: 99%